Video Narrative Exposure Therapy (NET) with children and young people who witnessed domestic violence: A naturalistic single case study series - Rocca, Fiammetta (2023)
Introduction Children and young people (CYP) who witnessed domestic violence (DV) can develop posttraumatic stress symptoms (PTSS) and other negative mental health outcomes. Narrative Exposure Therapy (NET) is a treatment for survivors of repeated or prolonged trauma which has been adapted for use with CYP and videoconferencing delivery. Despite the growing evidence for the use of NET with adults, fewer studies have been conducted using its child-friendly protocol. As a brief, NICE-recommended treatment that was specifically designed to address multiple traumas and appears to be tolerable, NET may be a good candidate for use with CYP experiencing trauma-related difficulties following DV-exposure.